(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to identify the effectiveness of using a proposed strategy according to the Fraunhofer model of knowledge management in the crystallized intelligence of second intermediate-class female students. To achieve the research objective, the following null hypothesis was formulated: "The average scores of the female students in the experimental group, who study according to the Fraunhofer model, and the control group, who studies based on the traditional method in the crystallized intelligence test do not differ statistically at the level (0.05)." The research community was selected on purpose, consisting of secondary and intermediate schools for girls within the General Directorate of Education of Baghdad/Al-Karkh II. The research sample included 61 female students; split into an experimental group included 33 female students and a control group included 28 female students. A crystallized intelligence test was developed to gather data for the investigation. The final version of the test included fifty objective items with four alternative answers. The results showed that the experimental group outperformed the control group in the crystallized intelligence test